QUALITY STANDARDS OF PRESS IMAGES IN NEWS WEBSITES - Refat Husni, Husni (ALBAHITH ALALAMI, 2019)
This research aims to reveal the quality standards available in press images published in the news sites, the Iraqi News Agency and Al-Mada Press for the period from: 1/9/2019, to: 30/9/2019. The research is a descriptive research, in which the researcher relied on the survey methodology to achieve its objectives. The research reached a number of results, most notably the weak role of photojournalists in the websites and the adoption of those the Internet as a source for obtaining press images published with news and reports through its pages, as well as the neglect of the standard Description/Comment below the press images, which plays an important function in explaining and interpreting them for users.